Harry Potter and the Sorcerer's Stone: Illustrated Version # 1 - Rowling, J. K.; Kay, Jim, (Illustrator) (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Witchcraft and Wizardry.
Originally published in a slightly different form in the United Kingdom by Bloomsbury in 1997 under title: Harry Potter and the philosopher's stone.
Sequel: Harry Potter and the Chamber of Secrets.
Keywords: Schools -- Fiction; Wizards -- Fiction; Magic -- Fiction; England -- Fiction